Export Marketing of Gum Arabic from Sudan - World Bank (2016)
This paper suggests that decontrol of the gum arabic export market could increase export revenues for Sudan and raise significantly the income of small scale farmers. One of the key commitments made by the Government of National Unity under the Joint Assessment Mission framework was to "abolish the export monopoly" over raw gum arabic. This commitment has not been implemented. The objective of this policy note is twofold: (a) to assess the impact of the Government policy for the export marketing of gum arabic, (b) to identify options for changing the current marketing arrangements in order to increase and stabilize gum exports, capture more value added in Sudan and provide producers with a larger share of export prices.